Analisis Keterbukaan Akses Informasi Keuangan dalam Peningkatan Penerimaan Pajak - Agus Bandiyono; Ayudya Purwani Putri (Universitas Pamulang, 2021)
This study aims to analyze the implementation of the Policy on Access to Financial Information for Tax Purposes and its role in increasing tax revenue at KPP Pratama Surakarta and the problems or obstacles faced in its implementation. The author uses a qualitative writing method with a literature study approach and field studies in its preparation. The results of this study indicate that the implementation of the Policy on Access to Financial Information for Tax Purposes contributes to the level of tax revenue at KPP Pratama Surakarta, although not significantly. Meanwhile, in its implementation there are still some obstacles experienced by the tax authorities, especially in terms of implementing requests and receipts of IBK (Information, Evidence, and/or Information) so that the Policy for Opening Access to Financial Information for Tax Purposes cannot be utilized optimally.